Joana Lopes' contributions to an ethical-poetic-aesthetics of the performing arts (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This article is a mix of a report on professional experiences, subsequent reflections and dialogue with bibliographies relating to part of Joana Lopes' professional career.The article has the character of a memory of lived experience, of a posthumous tribute to Joana Lopes as a director-pedagogue who is still little recognized in the singularity of her multiple, pioneering and precursory professional career. It is important here to discuss how much, in its creative process, the ethical-poetics co-realized among research people emerged in a contextualized aesthetics, complex, in a cultural miscegenation praxis with a transdisciplinary, complex, multifactorial and intersectional focus.
Keywords: Joana Lopes; women in the arts; theater; dance; choreodramaturg